2017
DOI: 10.1111/bju.13809
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of delay to cystoscopy and adequacy of investigations in patients with haematuria

Abstract: ObjectiveTo identify factors that impact on the timeliness and adequacy of haematuria evaluation. Patients and MethodsWe undertook a retrospective cohort study identifying patients who underwent cystoscopy for investigation of haematuria at our institution between 1 January 2015 and 31 December 2015. Data on patient demographics, smoking status, anticoagulation, type of haematuria and referring clinician were collected. Exclusion criteria included patient age <18 years, known history of bladder/urinary tract/r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 32 publications
6
26
0
Order By: Relevance
“…This strategy has the advantage of delivering a clear message to GPs precisely when they encounter a patient with haematuria, which for any individual GP is a relatively infrequent event. The high utilisation of MSU (96%) and upper tract imaging (82%) by GPs in the present study adds support to this approach, although we note lower utilisation of these investigations in a contemporaneous Australian series .…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This strategy has the advantage of delivering a clear message to GPs precisely when they encounter a patient with haematuria, which for any individual GP is a relatively infrequent event. The high utilisation of MSU (96%) and upper tract imaging (82%) by GPs in the present study adds support to this approach, although we note lower utilisation of these investigations in a contemporaneous Australian series .…”
Section: Discussionsupporting
confidence: 56%
“…Our present treatment delay compares particularly favourably, although this may simply reflect the fact that cystoscopy occurred at initial assessment in our series (and therefore waiting time to diagnostic cystoscopy did not contribute to treatment delay as it did in other series). Although not directly comparable, our median assessment delay of 23.5 days compares favourably to a contemporaneous Australian series of 305 patients referred for investigation of haematuria . In that comparative series the median delay to initial assessment of patients with visible haematuria was 33 days, with these patients experiencing an additional median delay of 27 days to cystoscopy .…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…However, a systematic review of the literature that we have recently undertaken has identified that patients with haematuria are inconsistently evaluated [2]. This finding was further corroborated in our study showing that many patients presenting to our institution with haematuria experience delays or gaps in their evaluations [3].A paucity of contemporary, evidence-based Australian guidelines, along with a lack of consensus among published guidelines worldwide may be important contributory factors. Thus, the AUA suggests cystoscopic evaluation for all patients with visible haematuria and those aged ≥35 years with nonvisible haematuria [4].…”
supporting
confidence: 74%
“…Hematuria is a clinical finding that can originate from anywhere in the urinary tract and can be the first sign of many diseases, including malignant diseases, of which prevalence may range from 4% to 19.3% (1,2). In clinical practice, hematuria comes out in two ways.…”
Section: Introductionmentioning
confidence: 99%